PERSEPSI ANGGOTA MASYARAKAT MENGENAI RESOSIALISASI DAN REHABILITASI MENCEGAH BEKAS NARAPIDANA MENJADI RESIDIVIST - Petrus Irwan Panjaitan; Radisman Saragih; Inri Januar (to-ra, 2019)
Abstract Imprisonment for prisoners by placing someone in a Penitentiary in Indonesia starting when Indonesian Penal Law (Wetbooek van strafrecht) is in force, after Indonesia independence, the nature of imprisonment in the Criminal Code is retaliation for someone's actions that harm others. After Indonesia's Independence, the orientation of the Criminal Prison underwent a change, spearheaded by Sahardjo, when he was Minister of Justice, Sahardjo's thoughts were expressed in a speech with the title : The Banyan tree under the legal guardian of the Pancasila Manipol Usdek at the University of Indonesia in 1963 while receiving the title Doctor HonorisCausa. Sahardjo said: prisoners are heretics who have the opportunity to repent and are empowered to become valuable people, one of them is re-socialisation and rehabilitation of prisoners, the aim is to restore the social relations of prisoners, so that they can finish their prison sentences, be able to return to work in the community, not to repeat the crime, thus the formation of prisoners is a form of the crime of missing independence to prevent prisoners from becoming recidivist. Keyword: public perception, convicted person, recidivist, penal law